Acute brain injury caused by occlusion of large vessel by COVID – 19 - Ruiz-Laos, Santiago Gerardo (2020)
In the 2019 coronavirus disease pandemic (COVID-19) caused by the SARS-CoV2 virus, the majority of patients present general and respiratory symptoms, some atypical gastrointestinal, cardiovascular, dermatological or neurological symptoms. In the case report of a 40-year-old male patient, without any important epidemiological history, diagnosed with COVID-19 by rapid immunological test, who presents with a sudden ischemic stroke. In the CT scan of the brain without contrast, a large ischemic area is evident in the left cerebral hemisphere in the middle cerebral artery territory, accompanied by edema. In patients with COVID-19, infected with the SARS-CoV2 coronavirus, the possibility of the patient having a cerebrovascular accident (CVA) should be taken into account, to allow adequate and timely management.